2018
DOI: 10.1074/jbc.r117.001561
|View full text |Cite
|
Sign up to set email alerts
|

Not just heads and tails: The complexity of the sperm epigenome

Abstract: Transgenerational inheritance requires mechanisms by which epigenetic information is transferred via gametes. Canonical thought holds that mammalian sperm chromatin would be incapable of carrying epigenetic information as post-translational modifications of histones because of their replacement with protamine proteins. Furthermore, compaction of the sperm genome would hinder DNA accessibility of proteins involved in transcriptional regulation and genome architecture. In this Minireview, we delineate the patern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…, there are data for transgenerational inheritance of diseases/dysfunctions including reproduction, obesity, psychiatric disorders from a variety of environmental stressors including vinclozolin, bisphenol A, atrazine bisphenol A plus phthalates (DEHP and DBP), permethrin plus DEET, methoxychlor, Jet fuel 8, phthalate (DEHP),dioxin, DDT, PCBs, tributyltin, nicotine, alcohol, calorie restriction, high‐fat diets, folate and stress. Mechanisms currently focus on a variety of epigenetic changes including DNA methylation, histone changes and non‐coding RNAs . Alterations in germ cells are required to transmit epigenetic information to future generations.…”
Section: Transgenerational Inheritancementioning
confidence: 99%
See 1 more Smart Citation
“…, there are data for transgenerational inheritance of diseases/dysfunctions including reproduction, obesity, psychiatric disorders from a variety of environmental stressors including vinclozolin, bisphenol A, atrazine bisphenol A plus phthalates (DEHP and DBP), permethrin plus DEET, methoxychlor, Jet fuel 8, phthalate (DEHP),dioxin, DDT, PCBs, tributyltin, nicotine, alcohol, calorie restriction, high‐fat diets, folate and stress. Mechanisms currently focus on a variety of epigenetic changes including DNA methylation, histone changes and non‐coding RNAs . Alterations in germ cells are required to transmit epigenetic information to future generations.…”
Section: Transgenerational Inheritancementioning
confidence: 99%
“…Mechanisms currently focus on a variety of epigenetic changes including DNA methylation, histone changes and non-coding RNAs. 21,27 Alterations in germ cells are required to transmit epigenetic information to future generations. Recent findings indicate that sperm are not that much different from somatic cells, in that they contain chromatin with modified histones in a three-dimensional architecture, some non-methylated DNA sites in promoter regions and promoters and enhancers in a primed state 27 and nc RNAs.…”
Section: Transgenerational Inheritancementioning
confidence: 99%
“…Representative genomic regions of the developmentally important loci, FOXB1, FOXC1 and SOX12 were also validated by ChIP PCR using H1T2 immunoprecipitated DNA as the template which con rmed signi cant enrichment of H1T2 in comparison to IgG immunoporecipiated chromatin control ( Fig 5B). Earlier studies have also demonstrated the nucleosomal retention and bivalent histone marks (H3K4me3/H3K27me3) to be signi cantly enriched at these loci of developmental importance, including HOX, SOX, FOX, TBX, PAX, CDX, and GATA family transcription factors (30,56). All together these results suggest a prominent role of the linker histone H1T2 in organizing speci c spermatid chromatin domains to potentially regulate transcription of several developmentally important embryonic genes.…”
Section: Validation Of H1t2 Chip Peaks Of Novel Target Genes By Chip-pcrmentioning
confidence: 58%
“…Representative genomic regions of the developmentally important loci, FOXB1, FOXC1 and SOX12 were also validated by ChIP PCR using H1T2 immunoprecipitated DNA as the template which con rmed signi cant enrichment of H1T2 in comparison to IgG immunoporecipiated chromatin control (Fig 5B). Earlier studies have also demonstrated the nucleosomal retention and bivalent histone marks (H3K4me3/H3K27me3) to be signi cantly enriched at these loci of developmental importance, including HOX, SOX, FOX, TBX, PAX, CDX, and GATA family transcription factors (33,59). All together these results suggest a prominent role of the linker histone H1T2 in organizing speci c spermatid chromatin domains to potentially regulate transcription of several developmentally important embryonic genes.…”
Section: Validation Of H1t2 Chip Peaks Of Novel Target Genes By Chip-pcrmentioning
confidence: 58%